Uji Coba Video Animasi Pencegahan Gagal Ginjal pada Siswa Siswi SDN 84 Kendari - Rika Astrika Reski; Ruslan Majid; Hartati Bahar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Excessive consumption of carbonated drinks and lack of water intake are risk factors that can cause impaired kidney function, characterized by increased excretion of albumin in the urine and thickening of the renal medulla. Therefore, effective education is needed for elementary school children, one of which is through animated video media to increase their understanding and awareness in preventing consumption of carbonated drinks and maintaining kidney health from an early age. The aim of this activity is to measure the effectiveness of animated videos in increasing SDN 84 Kendari's knowledge of the dangers of carbonated drinks to prevent kidney failure. The sample in this study was 105, with a p-value of knowledge (0.000) < alpha (0.05), the Wilcoxon Signed Ranks T-test results showed an increase in knowledge after exposure to the animated video to students at SDN 84 Kendari.